Lo spazio rurale come risorsa strategica in Paesaggi coltivati, paesaggio da coltivare di Alessandra Cazzola - Maino, Elisabetta (Ri-Vista. Research for landscape architecture, 2015)
A. Cazzola emphasizes on a new culture of open areas, where the rural space is understood as a strategic resources to landscape redevelopment. In the book ‘Paesaggi coltivati, paesaggio da coltivare. Lo spazio agricolo dell’area romana tra campagna, territorio urbanizzato e produzione’ are outlined methodological criteria and address for a lecture and a planning of rural landscape that can offer either sustainable food or non-commercial products, addressed to protection and environmental compensation, to social building, to safeguard of cultural identities and rural landscape revitalization. Everything through actions calibrated on local landscape specificity, either traditional identity signs or new elements, sometimes dissonant and lacerating.